RUIN AS RESURRECTION: AN INTERSECTIONAL FEMINIST READING OF THE FALLEN WOMAN IN VICTORIAN LITERATURE - Javier, Wenona Bea (International Journal of Humanity Studies (IJHS), 2025)
In so-called civilized societies, women who defy traditional norms or engage in “immoral” behavior are harshly judged and excluded. This dynamic is evident in Thomas Hardy’s The Ruined Maid, Augusta Webster’s A Castaway, and Émile Zola’s Nana, where female characters are portrayed as morally transgressive and socially irredeemable, reinforcing rigid binaries between virtue and vice. Applying Kimberlé Crenshaw’s theory of intersectionality (1989), this paper explores how class, gender, societal expectations, and sexual politics converge to shape these women’s identities and societal reception. Findings reveal that the “fallen” women in the Victorian literary works resist confinement through economic agency, self-awareness, and even spectacle. Rather than passive victims, they emerge as complex figures whose lives defy singular interpretation. This study critiques the moralistic frameworks of Victorian literature while foregrounding intersectionality as a critical method for dismantling dominant narratives that persist in shaping modern gender norms. Ultimately, it calls for more liberating readings of women’s transgressions across time.